2019
DOI: 10.1002/2211-5463.12655
|View full text |Cite
|
Sign up to set email alerts
|

XBP1 inhibits mesangial cell apoptosis in response to oxidative stress via the PTEN/AKT pathway in diabetic nephropathy

Abstract: Diabetic nephropathy ( DN ) is a complication of diabetes mellitus ( DM ) that frequently results in renal disease, and is characterized by a variety of symptoms, including albuminuria. It has been shown that apoptosis of glomerular mesangial cells ( MC s) can aggravate albuminuria and contribute to the development of diabetic glomerulosclerosis. Hence, determination of the mechanisms leading to MC apoptosis may help us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…DEX treatment could reverse the changes described above; studies have also found that PTEN may be a kind of protective gene in the kidney [23][24][25][26][27] . High expression of PTEN can negatively regulate the PI3K/Akt pathway, inhibit the activation of Akt, improve the phenotype of renal podocytes, and reduce damage to renal podocytes [28] .In early DN, as glomerular damage increases, the expression of PTEN gradually decreases, suggesting that PTEN has a certain correlation with glomerular damage [29][30][31][32] . To con rm the exact mechanism of PTEN in podocyte injury, after silencing the PTEN gene, we found that the expression of the downstream signaling pathway protein AKT increased,podocyte autophagy was signi cantly inhibited, and the expression of the LC3B protein signi cantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…DEX treatment could reverse the changes described above; studies have also found that PTEN may be a kind of protective gene in the kidney [23][24][25][26][27] . High expression of PTEN can negatively regulate the PI3K/Akt pathway, inhibit the activation of Akt, improve the phenotype of renal podocytes, and reduce damage to renal podocytes [28] .In early DN, as glomerular damage increases, the expression of PTEN gradually decreases, suggesting that PTEN has a certain correlation with glomerular damage [29][30][31][32] . To con rm the exact mechanism of PTEN in podocyte injury, after silencing the PTEN gene, we found that the expression of the downstream signaling pathway protein AKT increased,podocyte autophagy was signi cantly inhibited, and the expression of the LC3B protein signi cantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…diabetic nephropathy (dn) is becoming the most pervasive complication for both types i and ii diabetes, and is also the major cause of end-stage renal disease in the majority of developed and developing countries (1). clinically, dn is characterized by mesangial hypertrophy, mesangial cell (Mc) proliferation, albuminuria, extracellular matrix (ecM) accumulation and kidney fibrosis (2,3). It has been recognized that the glomerular Mcs and ecM accumulation are involved in a variety of biological events (4).…”
Section: Introductionmentioning
confidence: 99%
“…Cell apoptosis is an important aspect of DN pathogenesis [16]. Two vital molecular signaling pathways are involved in cell apoptosis, including the intrinsic pathway and the extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%